Defective Expression of Scavenger Receptors in Celiac Disease Mucosa - Cupi, Maria Laura (Public Library of Science, 2014)
Celiac disease (CD) is a gluten sensitive enteropathy characterized by a marked infiltration of the mucosa with immune cells, over-production of inflammatory cytokines and epithelial cell damage. The factors/mechanisms that sustain and amplify the ongoing mucosal inflammation in CD are not however fully understood. Here, we have examined whether in CD there is a defective clearance of apoptotic cells/bodies, a phenomenon that helps promote tolerogenic signals thus liming pathogenic responses. Accumulation of apoptotic cells and bodies was more pronounced in the epithelial and lamina propria compartments of active CD patients as compared to inactive CD patients and normal controls. Expression of scavenger receptors, which are involved in the clearance of apoptotic cells/bodies, namely thrombospondin (TSP)-1, CD36 and CD61, was significantly reduced in active CD as compared to inactive CD and normal mucosal samples. Consistently, lamina propria mononuclear cells (LPMC) of active CD patients had diminished ability to phagocyte apoptotic cells. Interleukin (IL)-15, IL-21 and interferon-γ, cytokines over-produced in active CD, inhibited the expression of TSP-1, CD36, and CD61 in normal intestinal LPMC. These results indicate that CD-related inflammation is marked by diminished clearance of apoptotic cells/bodies, thus suggesting a role for such a defect in the ongoing mucosal inflammation in this disorder.